The United States Cycle in Private Fixed Investment, 1946-50 - Blyth, Conrad A. (The Review of Economics and Statistics, 1956)
IN an earlier article it was shown that there was a fall in private fixed investment in 1948-50 which played a considerable part, and possibly the most important part, in inducing the fall in production and reduced inventory investment in the United States from late in 1948 until early I950.1 It is proposed to examine here aspects of private fixed investment during the period I946-50 which have some theoretical significance. When the official investment statistics are broken down by sector and industry, a considerable variety of cyclical patterns emerges. Rates of postwar expansion and dates of turning points differ considerably. The dates of turning points of total investment have little significance unless they are viewed as averages; this in itself is not a particularly novel conclusion. This pattern in turning points becomes significant when considered in relation to the more general causes of the postwar expansion in investment, and in relation to both the immediate and deeper influences that may have checked the expansion. When the statistics of investment in producers' durable equipment are examined from the point of view of type of equipment, a similar variety of cyclical patterns emerges, which because of the clearness of the pattern and the greater reliability of the statistics can be related in quite a precise way to the causes of the expansion or, more generally, to the determinants of the rate of investment. In summary form, the conclusions drawn from the statistical studies are as follows. On most types of durable goods, the peak and ensuing decline in expenditures occurred earlier (i.e., more quickly after the end of the war) the greater the expansion in expenditures during the war. The rates of expansion just before the war, the rates of expansion in the postwar period, and relative price changes do not alter this conclusion, although they are needed as elements to supplement the exDlanation. The sector analysis, which includes private new construction, supports these conclusions, although it is obvious and well known that special factors influenced investment on farms, railroads, public utilities, and residential construction. Neither the annual change in output, the annual level of output, nor the level of corporate profits can be satisfactorily related to the changes in the rate of fixed investment over the period in ways which would provide explanations of the rate of investment. The set of circumstances governing the changes in the rate of investment after the war would appear to be (a) the different wartime rates of investment of different corporations, industries, and sectors; and (b) the different wartime rates of investment in different types of plant and equipment. Generally, the less a firm had invested during the war, or the lower the production of a particular type of equipment (presumably because of the wartime allocation of resources), the longer was the period after the war during which the firm's investment, or investment in the particular type of equipment, increased. The deferred investment demand of the war years or the deferred replacement investment was a large enough proportion of total investment for the gradual falling off of the former in I948-49 to cause a change in the total. The absence of any noticeable accelerator or profit relations except possibly a short-period accelerator effect in the middle of I 949suggests that that investment which was not specifically deferred replacement investment continued to increase after 1948. It is this which explains the recovery in total investment expenditures in early I950, and which partly explains the short lived character of the I949 slump.2 These conclusions have been based upon a study of the available official statistics. Annual figures have been used throughout, both